The role of surface analysis in the strategies for conservation of metallic artefacts from the Mediterranean Basin1. (2nd April 2014) - Angelini, E.; Batmaz, A.; de Caro, T.; Faraldi, F.; Grassini, S.; Ingo, G. M.; Riccucci, C.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Conservation and valorization of cultural heritage is a fundamental element and an essential mission of the Mediterranean countries where most of the ancient and fascinating witnesses of human art and creativity are conserved. A large component of this cultural heritage consists of material cultural assets that are often exposed to harmful long‐term effects of environmental pollution, inappropriate handling, and intrinsic chemical–physical instability. Many risks can be mitigated, provided that there is a proper knowledge of the materials involved and of their degradation processes and adequate means to counteract these processes or to restore the materials. The employment of surface analysis can be extremely useful for the development of both tailored conservation procedures and methodologies as a function of the different degradation mechanisms that affect the artefacts, as well as for the monitoring of the conservation state and the identification of the manufacturing techniques. Several metallic artefacts coming from different archaeological sites of the Mediterranean Basin have been examined: weapons found during the excavation of the Ayanis fortress of the Urartu civilization (Lake Van, Anatolia, Turkey) and silver and bronze artefacts found at Tharros (Italy), a Phoenician–Carthaginian and then Roman city located along the Sardinian coast. They have been studied by means of the combined use of selected area X‐ray photoelectron spectroscopy, X‐ray diffraction, optical microscopy, and scanning electron microscopy + energy dispersive spectrometry. The surface analysis techniques are able to give important contributions in the identification of chloride ions that may dramatically affect the chemical–physical stability of the copper‐based artefacts, thus allowing developing proper conservation strategies, as well as in the identification of the presence of mercury on gilded artefacts, thus giving information on the manufacturing technique. Copyright © 2014 John Wiley & Sons, Ltd.